2012 International Symposium on Wireless Communication Systems (ISWCS) 2012
DOI: 10.1109/iswcs.2012.6328536
|View full text |Cite
|
Sign up to set email alerts
|

An epidemic game between contents in a wireless network

Abstract: Abstract-Consider a town with N competing sources of content where each one wishes to disseminate its own content and thus to make its content available to as many destination users as possible. A content here may stand for information about somoe cultural event or the list of hotels in town or the wheather report. The dissemination to the potential destination is done through a fleet of M mobile relays. The rate of dissemination of content of a given source to its potential destinations depends on how many re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…] is not necessarily true, the N -intertwined deterministic model (4) serves as an approximation of the stochastic network model (7). Indeed, it is shown that the expected values p i in (4) are upper bounds on the actual probabilities given by ( 7) [22,97,102,134].…”
Section: Stochastic Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…] is not necessarily true, the N -intertwined deterministic model (4) serves as an approximation of the stochastic network model (7). Indeed, it is shown that the expected values p i in (4) are upper bounds on the actual probabilities given by ( 7) [22,97,102,134].…”
Section: Stochastic Modelsmentioning
confidence: 99%
“…Indeed, it is shown that the expected values p i in (4) are upper bounds on the actual probabilities given by ( 7) [22,97,102,134]. Furthermore, [133] investigates how accurate the deterministic approximations (4) are in describing the stochastic model (7).…”
Section: Stochastic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Content dissemination in social networks has been extensively studied, especially in the context of marketing, as surveyed in [13] and papers cited therein, or yet the more recent publication [12]. Several game theoretic approaches have been proposed to model competition in dissemination between contents, be they in wireless networks composed of sources and relays [2] or in the context of social networks where competition is on popularity and advertisement spaces such as in [3], [4].…”
Section: Introductionmentioning
confidence: 99%